Women-owned MSMEs and Financial Inclusion in Egypt - Khairy, Noheir Ahmed (AUC Knowledge Fountain, 2019)
In Egypt, Micro Small and Medium Enterprises (MSMEs) play a crucial role in the economy, with their contribution to Gross Domestic Product (GDP) and employment. Despite being the backbone of the economy, they are constantly confronted with challenges in the business environment. Primary amongst these challenges is limited access to formal financial capital at an affordable interest rate leading them to depend on other sources of finance like savings and informal financial services. Women-owned MSMEs especially, have been found to face more challenges in terms of financial accessibility and exclusion from the formal financial market. This work highlights the extent of financial inclusion in Egypt with respect to not only access, but also usage and quality of financial service problems faced by MSMEs in general and women-owned businesses in particular. The analysis of the study follows the comprehensive framework of financial inclusion including access, usage and quality of financial products and services. The findings of this research reveal that while women-owned MSMEs face certain challenges similar to those of their male-owned counterparts, the severity of their challenges is more pronounced by virtue of they being women-owned. Specific constraints faced by women includes risk aversion of banks, lack of financial services and products targeting women-owned MSMEs, lack of collateral and low levels of financial awareness and financial literacy. Whilst a number of interventions have been put in place by the Central Bank of Egypt (CBE) and the Financial Regulatory Authority (FRA) to address the issue of financial inclusion within the MSME sector, most of them do not take gender into consideration. The study recommends continuing supporting MSMEs financial inclusion especially women-owned MSMEs through addressing non-price barriers like supporting a secured collateral framework, raising the capabilities of financial institutions to better serve women-owned MSMEs and focusing on raising financial awareness and literacy among women-owned MSMEs.